2019
DOI: 10.1021/acs.joc.9b00948
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-Cyano-3-acylnaphthalenes via Formal [4+2] Benzannulation of 2-(2-Alkynylphenyl)acetonitriles and Alkynones

Abstract: Effective transition-metal-free formal [4+2] benzannulation for the preparation of 1-cyano-3-acylnaphthalenes from 2-(2-alkynylphenyl)­acetonitriles and alkynones through sequential C–C bond coupling has been developed. This protocol is characterized by mild conditions, excellent functional group tolerance, complete regioselectivity, and atom economy. The plausible mechanism, gram-scale synthesis, and further transformations of the product were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The synthesis of polysubstituted naphthalenes (Scheme 14) was investigated by Wang et al [20] The expected product was obtained with 56% yield. Further experiments for screening of the reaction have been performed and it was found that a higher yield of the product was obtained with 10 mol% loading of LiO t Bu, and hence, it is considered as the ideal condition for the reaction.…”
Section: Carbon-carbon Bond Forming Reactionsmentioning
confidence: 99%
“…The synthesis of polysubstituted naphthalenes (Scheme 14) was investigated by Wang et al [20] The expected product was obtained with 56% yield. Further experiments for screening of the reaction have been performed and it was found that a higher yield of the product was obtained with 10 mol% loading of LiO t Bu, and hence, it is considered as the ideal condition for the reaction.…”
Section: Carbon-carbon Bond Forming Reactionsmentioning
confidence: 99%
“…And MK‐0633, [12] is a promising 5‐lipoxygenase inhibitor ( Scheme 1 ,a ). Over the past decades, many efforts have been made to construct such motifs [5,6,13–21] . However, the development of general and efficient methodologies remains challenging and is still highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…11 In 2007, the Deng group reported the base-mediated [4+2] benzannulation of vinyl malononitriles and nitroolefins. 12 Since then, various types of benzannulation such as [3+2+1], 13,14 [3+3], 1517 and [4+2] 18 have been uncovered. As an alternative, Wang 19 and Ye 20 groups independently reported a benzannulation route by N -heterocyclic carbene catalysis.…”
Section: Introductionmentioning
confidence: 99%